COMPARATIVE EVALUATION OF INTRAVENOUS DEXMEDETOMIDINE AND MAGNESIUM SULFATE FOR ATTENUATION OF PRESSOR RESPONSE DURING LARYNGOSCOPY AND ENDOTRACHEAL INTUBATION: A RANDOMIZED CONTROL STUDY - SARA MARY THOMAS; SUJAY GHETIYA; ARPIT SHAH; JIGISHA MEHTA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The present study compared the efficacy of intravenous dexmedetomidine versus intravenous magnesium sulfate for attenuation of pressor response during laryngoscopy and endotracheal intubation. Methods: This prospective randomized study was conducted among 52 patients undergoing general anesthesia. Patients were divided into two groups – Group D and Group M of 26 patients each. Group D received Inj. Dexmedetomidine 1 mcg/kg intravenous (IV) and Group M received Inj. Magnesium sulfate 30 mg/kg IV. diluted in 100 mL normal saline over 30 min before induction of general anesthesia. Hemodynamic parameters such as heart rate (HR), systolic blood pressure, diastolic blood pressure, and mean arterial pressure were compared between both the groups till 7 min after intubation. Results: Demographic parameters did not differ significantly between the groups (p>0.05). Group D showed significantly lower HR and blood pressure after induction, at intubation and at 1, 3, 5, and 7 min post-intubation compared to Group M (p<0.05). Conclusion: Our study concluded that administering dexmedetomidine intravenously at a dose of 1 mcg/kg effectively reduced the sympathetic response to laryngoscopy and intubation as compared to magnesium sulfate 30 mg/kg intravenously.